Development and feasibility assessment of a virtual reality-based aerobic exercise program with real-time pulse rate monitoring on hemodynamic and arterial stiffness in healthy people: a pilot study - Yuenyongchaiwat, Kornanong; Sermsinsathong, Natsinee; Songsorn, Preeyaphorn; Charususin, Noppawan; Buranapuntalug, Sasipa; Buekban, Chatchai; Thanawattano, Chusak (Frontiers in Digital Health, 2024)
Introduction Virtual reality (VR) exercises are reportedly beneficial as a physical activity tool for health promotion and rehabilitation, and can also help individuals exercise under professional supervision. We developed and investigated the potential feasibility of a VR-based aerobic exercise program using the XBOX ONE console and Kinect sensor with real-time pulse rate monitoring. The VR setting consisted of two-dimensional (2D) environments via computer, laptop, or television screens. In addition, the study investigated the potential feasibility of the VR-based exercise program on hemodynamic response and arterial stiffness in healthy participants of various ages. Methods Healthy participants (n = 30) aged > 18 years were enrolled in the VR exercise-based program. All participants were required to wear a polar heart rate (HR) monitor set for moderate-intensity exercise, targeting 40%–59% of their HR reserve. Hemodynamic and arterial stiffness (pulse wave velocity) were noninvasively measured. The Borg scale rate of perceived exertion (RPE) was also assessed. Results Following a VR-guided exercise routine, all participants performed moderate-intensity exercise with no adverse health outcomes during or after the exercise. The effects of VR-based aerobic exercise extended beyond enhanced central hemodynamic and arterial stiffness. However, neither hemodynamic nor arterial stiffness showed significant differences before and after the VR exercise, except for a higher RPE response following the exercise program. Conclusion VR-based aerobic exercise with pulse rate monitoring is a promising physical activity tool to induce physiological changes and impact dyspnea scales and is also feasible for administration to healthy populations.